Bela Beli Kulon Progo as A Policy for Strengthening The Capacity of Local Economy - Nunuk Dwi Retnandari (Indonesian Association for Public Administration, 2017)
One of the reasons for the State’s presence in society is due to market’s failure in providing its citizens with better welfare. The local economy2 that serves as a source of welfare for most Indonesian communities is placed under very strenuous conditions when having to confront capitalist economy. Remarkably diﬀering backgrounds and resources create a highly imbalanced bargaining position. There have been numerous policies in the form of local economic development programs that have been carried out by Indonesia. However, the reality indicates that as of current the contribution of local economies in the GDP remains at approximately 50%. The interventions employed using a global approach, did not consider the specification of issues confronted by local economies, the State intervention performance metrics were very simple (activities) and there was a lack of serious evaluation regarding the intervention, which led to it not bearing much fruitful results. It was the Kulon Progo Regency which developed the concept of empowering local economy by using a specific approach confronted by the local economy. The policy is known as “Bela Beli Kulon Progo”. This article discusses the process undertaken by the Kulon Progo Regency in implementing the “Bela Beli Kulon Progo” movement which succeeded in boosting local economic development performance.